Systems for working faster (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. An unorganised and inefficient tech stack wastes a significant amount of time and money. Today, you will learn about some of the most effective and most used software platforms for project management tasks. That includes broader management tools, creative project management apps, and the best communication software. In this track, we look at where you can find objective reviews for productivity tools as well as looking at important related topics around software integration, automation, transparency, and ownership. Learning Objectives Learn about different types of project management software and systems, as well as communication tools and video software Learn which type of app, or ecosystem, would be the best fit for you and/or your organization.